Metabolic Profiling of Rhizobacteria Serratia plymuthica and Bacillus subtilis Revealed Intra- and Interspecific Differences and Elicitation of Plipastatins and Short Peptides Due to Co-cultivation - Menezes, Riya C.; Piechulla, Birgit; Warber, Dörte; Svatoš, Aleš; Kai, Marco (Frontiers in Microbiology, 2021)
Rhizobacteria live in diverse and dynamic communities having a high impact on plant growth and development. Due to the complexity of the microbial communities and the difficult accessibility of the rhizosphere, investigations of interactive processes within this bacterial network are challenging. In order to better understand causal relationships between individual members of the microbial community of plants, we started to investigate the inter- and intraspecific interaction potential of three rhizobacteria, the S. plymuthica isolates 4Rx13 and AS9 and B. subtilis B2g, using high resolution mass spectrometry based metabolic profiling of structured, low-diversity model communities. We found that by metabolic profiling we are able to detect metabolite changes during cultivation of all three isolates. The metabolic profile of S. plymuthica 4Rx13 differs interspecifically to B. subtilis B2g and surprisingly intraspecifically to S. plymuthica AS9. Thereby, the release of different secondary metabolites represents one contributing factor of inter- and intraspecific variations in metabolite profiles. Interspecific co-cultivation of S. plymuthica 4Rx13 and B. subtilis B2g showed consistently distinct metabolic profiles compared to mono-cultivated species. Thereby, putative known and new variants of the plipastatin family are increased in the co-cultivation of S. plymuthica 4Rx13 and B. subtilis B2g. Interestingly, intraspecific co-cultivation of S. plymuthica 4Rx13 and S. plymuthica AS9 revealed a distinct interaction zone and showed distinct metabolic profiles compared to mono-cultures. Thereby, several putative short proline-containing peptides are increased in co-cultivation of S. plymuthica 4Rx13 with S. plymuthica AS9 compared to mono-cultivated strains. Our results demonstrate that the release of metabolites by rhizobacteria alters due to growth and induced by social interactions between single members of the microbial community. These results form a basis to elucidate the functional role of such interaction-triggered compounds in establishment and maintenance of microbial communities and can be applied under natural and more realistic conditions, since rhizobacteria also interact with the plant itself and many other members of plant and soil microbiota.